2022
DOI: 10.1039/d1ta09769e
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive and ultra-stretchable zwitterionic liquid hydrogel-based sensor as anti-freezing ionic skin

Abstract: Soft conductors show great promise in multifunctional sensor applications. However, both electronically and ionically conductive materials are often vulnerable during large deformation or at low temperatures, leading to reduced sensitivity,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 59 publications
0
55
0
Order By: Relevance
“…As a kind of common products in industry, the low cost of epoxy glycidyl ethers would benefit for the further development of robust adhesives (0.05–7.04 USD/g price obtained from Aladdin Biochemical Technology Co., Ltd. would be cheaper in industry from Figure S10a, Supporting Information). Also, those natural polyphenolic adhesives exhibited good low temperature (i.e., the adhesion strength of TA-epoxy adhesives in 25 to −196 °C was stronger than many antifreeze adhesives from Figure S10b, Supporting Information) and simple preparation process compared to many established catechol-based adhesives, , which could be widely used in several kinds of device repairment (i.e., chemical, petroleum, wood, metal, glass, plastic, rubber, and other industries) under different temperatures. Above all, the natural polyphenol-epoxy adhesives developed in the current study could achieve superior performances in different aspects (e.g., robust adhesion, universal adhesion, low price, simple process, low-temperature resistance, and various solvent resistance performances), which were quite interesting for the chemical and industrial fields.…”
Section: Resultsmentioning
confidence: 99%
“…As a kind of common products in industry, the low cost of epoxy glycidyl ethers would benefit for the further development of robust adhesives (0.05–7.04 USD/g price obtained from Aladdin Biochemical Technology Co., Ltd. would be cheaper in industry from Figure S10a, Supporting Information). Also, those natural polyphenolic adhesives exhibited good low temperature (i.e., the adhesion strength of TA-epoxy adhesives in 25 to −196 °C was stronger than many antifreeze adhesives from Figure S10b, Supporting Information) and simple preparation process compared to many established catechol-based adhesives, , which could be widely used in several kinds of device repairment (i.e., chemical, petroleum, wood, metal, glass, plastic, rubber, and other industries) under different temperatures. Above all, the natural polyphenol-epoxy adhesives developed in the current study could achieve superior performances in different aspects (e.g., robust adhesion, universal adhesion, low price, simple process, low-temperature resistance, and various solvent resistance performances), which were quite interesting for the chemical and industrial fields.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by nature and living organisms (e.g., octopuses, jelly-sh, and muscle tissue), so robots have gained considerable attention. 1,2 Compared to robots with rigidly connected materials, so robots do not require related joints and can perform continuous deformability to mimic biological complex motions, which have potential application prospects in articial muscles, 3,4 military services, 5,6 smart health care, [7][8][9] and surgical instruments. 10,11 Optimal so robots should be composed of advanced sensors and smart actuators.…”
Section: Introductionmentioning
confidence: 99%
“…Various endeavors have been performed in the development of stretchable ionic conductors loaded with ILs up to now, and encouraging progress has been made. For instance, Zhang et al fabricated an ionic conductive hydrogel that exhibits high strain sensitivity over a broad workable range with methacrylate lysine monomers and zwitterionic IL . Koo et al demonstrated a low-power, deformable, and dynamic multicolor electrochromic skin by incorporating IL in polyurethane (PU) .…”
Section: Introductionmentioning
confidence: 99%